Response of rapeseed to nitrogen fertilisation in a mediterranean environment - Rodrigues, M.A. (2011)
Portugal needs urgency to increase the production of vegetable oils to be able to meet the mandatory 10% minimum target to be achieved by all EU member states for the proportion of biofuels in petrol and diesel consumption by 2020 (Directive 2009128/EC). Rapeseed oil is the main raw material used in Europe for the manufacture of biofuels. Portugal, however, does not produce rapeseed oil, in spite of some studies having indicated that there are favourable ecological conditions to do this throughout the country [I, 2]